Kimura’s Disease: A Rare Cause of Unilateral Tonsillar Enlargement - Khanal, Prakash; Shrestha, Agya (Case Reports in Otolaryngology, 2021)
Introduction. Kimura’s disease is a rare inflammatory disorder of unknown cause, commonly seen in young Asian males. Case Report. A 61-year-old male patient presented with a history of right tonsillar mass and cervical lymphadenopathy. The patient underwent hematological investigation and imaging followed by resection of tonsillar mass. Based on histopathological and subsequent immunohistochemistry reports, the case was diagnosed as Kimura’s disease of the tonsil. Discussion. Kimura’s disease commonly presents as painless subcutaneous masses in the head and neck region or cervical lymphadenopathy. Kimura’s disease presenting as a tonsillar mass is a very rare condition. Patients usually have peripheral eosinophilia and elevated levels of serum IgE. The diagnosis is based on the clinical and histopathologic findings in a biopsy of the mass and/or lymph node along with elevated peripheral eosinophil and serum IgE level. Conclusion. The clinical presentation of Kimura’s disease is highly variable. Kimura’s disease should be considered as a differential diagnosis in patients presenting with a tonsillar mass. A high index of suspicion along with histopathological examination helps in the early diagnosis and management. Surgical excision is the treatment of choice.